The role of SOX family members in solid tumours and metastasis. (December 2020) - Grimm, Daniela; Bauer, Johann; Wise, Petra; Krüger, Marcus; Simonsen, Ulf; Wehland, Markus; Infanger, Manfred; Corydon, Thomas J.
Abstract: Cancer is a heavy burden for humans across the world with high morbidity and mortality. Transcription factors including sex determining region Y (SRY)-related high-mobility group (HMG) box (SOX) proteins are thought to be involved in the regulation of specific biological processes. The deregulation of gene expression programs can lead to cancer development. Here, we review the role of the SOX family in breast cancer, prostate cancer, renal cell carcinoma, thyroid cancer, brain tumours, gastrointestinal and lung tumours as well as the entailing therapeutic implications. The SOX family consists of more than 20 members that mediate DNA binding by the HMG domain and have regulatory functions in development, cell-fate decision, and differentiation. SOX2, SOX4, SOX5, SOX8, SOX9, and SOX18 are up-regulated in different cancer types and have been found to be associated with poor prognosis, while the up-regulation of SOX11 and SOX30 appears to be favourable for the outcome in other cancer types. SOX2, SOX4, SOX5 and other SOX members are involved in tumorigenesis, e.g. SOX2 is markedly up-regulated in chemotherapy resistant cells. The SoxF family (SOX7, SOX17, SOX18) plays an important role in angio- and lymphangiogenesis, with SOX18 seemingly being an attractive target for anti-angiogenic therapy and the treatment of metastatic disease in cancer. In summary, SOX transcription factors play an important role in cancer progression, including tumorigenesis, changes in the tumour microenvironment, and metastasis. Certain SOX proteins are potential molecular markers for cancer prognosis and putative potential therapeutic targets, but further investigations are required to understand their physiological functions.